2002
DOI: 10.1002/ijc.10370
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network considerably improves the diagnostic power of percent free prostate‐specific antigen in prostate cancer diagnosis: Results of a 5‐year investigation

Abstract: Our study was performed to evaluate the diagnostic usefulness of %fPSA alone and combined with an ANN at different PSA concentration ranges, including the low range 2-4 ng/ml, to improve the risk assessment of prostate cancer. A total of 928 men with prostate cancer and BPH without any pretreatment of the prostate in the PSA range 2-20 ng/ml were enrolled in the study between 1996 and 2001. An ANN with input data of PSA, %fPSA, patient's age, prostate volume and DRE status was developed to calculate the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
(66 reference statements)
1
24
0
5
Order By: Relevance
“…This may be the best possible approach with the advent of artificial neural networks, which are capable of weighing the influence of each factor in determining the final result. 56 Data from the two different periods showed increasing prostate volume in patients with PCa and BPH within the last years. Because no method was changed, it is difficult to explain this result.…”
Section: Discussionmentioning
confidence: 97%
“…This may be the best possible approach with the advent of artificial neural networks, which are capable of weighing the influence of each factor in determining the final result. 56 Data from the two different periods showed increasing prostate volume in patients with PCa and BPH within the last years. Because no method was changed, it is difficult to explain this result.…”
Section: Discussionmentioning
confidence: 97%
“…Combined use of several variables has been shown to reduce the number of false-positive PSA results more efficiently than single use of the proportion of free PSA. [12][13][14][15][16][17][18][19] However, LR or neural network algorithms for prostate cancer detection have not been studied prospectively; i.e., use of algorithm outcomes for making real-life biopsy decisions has not been reported. We simulated a prospective setting by using earlier subjects as training data and later ones for testing of the algorithms.…”
Section: Abstract: Prostate Cancer; Screening; Logistic Regression; mentioning
confidence: 99%
“…DISCUSSION Earlier studies showed that algorithms based on total PSA, free PSA, DRE and prostate volume can be used to reduce the number of false-positive PSA results in screening for prostate cancer more efficiently than the proportion of free PSA alone. [12][13][14][15][16][17][18][19] Despite this, there are no reports on the use of such algorithms in a prospective setting. Our study included 1,775 screen-positive men from the 3 largest participating centers in the European Randomized Study of Screening for Prostate Cancer, 20 -22 making it the largest study on predicting prostate biopsy results in the PSA range 4 -10 g/l using LR and neural networks.…”
Section: Clinical Stage and Histopathologic Gradementioning
confidence: 99%
“…To compare the programs, we used a previously described dataset of 928 men with prostate cancer (n ϭ 606) and benign prostatic hyperplasia (n ϭ 322) and subgroups of this population (3 ). ROC analyses of total prostate-specific antigen (tPSA), 3 free PSA (fPSA), the ratio of fPSA to tPSA (fPSA/tPSA), and of other values calculated by an artificial neural network approach with the mentioned dataset (3 ) were carried out to estimate the advantages and disadvantages of each program.…”
Section: Datasets For Roc Analysismentioning
confidence: 99%